Pembangkitan Cahaya Virtual Dinamis Pada Augmented Reality Menggunakan Canny Edge Detection, Contour Finding Dan Unity Light Renderer - Yoze Rizki; Mochamad Hariadi (JURNAL FASILKOM (teknologi inFormASi dan ILmu KOMputer), 2019)
ABSTRACT In Augmented Reality, the object lighting factor becomes a matter of concern. Lighting of virtual objects that have been manually generated is considered less realistic. Real time dynamic light generation system is needed to make an Augmented Reality application more realistic. With the generation of dynamic virtual light, AR objects lighting can be generated at the position and intensity of light colors that match the light source from the real environment around the AR object. In this study a light generation system was made with reference to the color intensity of light and the direction of light in the real environment. Retrieval of the light source color is done by retrieving the color value of a pixel with the highest intensity of brightness.Retrieval of the position of the light source is done by determining the axis of the pixel on the marker image which has the highest brightness level. From the results of 1st experiment through 4th experiment, the percentage of position equality is 92.10% from the actual position. From the results of the color experiment, it was found that the percentage of the light color of the results compared with the color of the source light was 66.66%. Low percentage of color similarity caused by light reflection on high gray value on marker (> 180), and other light sources that affect the light output generated by the Unity3D game engine in the simulation.